Evaluation of antiepileptic properties of herbal mix of different combinations by PTZ-induced mouse model - P.S. Venkatesan; S. Sundaresan; M. Eswarya; M. Madhavaselvi; R. Renuka (Phytomedicine Plus)
Background: Epilepsy is a neurological disorder characterized by convulsive seizures. Between 50 and 70 million people worldwide are impacted, and safer medications with superior anticonvulsant qualities and greater accessibility are still needed. Antiepileptic drug (AED) side effects continue to be a significant concern despite advances in pharmacotherapy, as they can lower quality of life and adherence. Herbal medicines are becoming more and more popular as complementary and alternative therapies as a result. Methods: Using a mouse seizure model caused by PTZ (Pentylenetetrazole) of dose 120 mg/kg.b.wt, this study examines the anticonvulsant efficacy of a traditional medicinal plant called Withania somnifera, Matricaria recutita and Evolvulus alsinoides which are commonly called as Ashwagandha, Chamomile and Morning glory respectively. The herb was mixed with 1.5 % Carboxymethyl cellulose (CMC) and given to mice with various dosage levels and in combination. Results: The study demonstrates that Evolvulus alsinoides, Withania somnifera, and Matricaria recutita, possesses significant anticonvulsant properties in a PTZ-induced seizure model in mice. Combination of all three showed highest latency of 168.25 ± 30.4s and seizure period of 3.82 ± 7.65 s